EARTH, MY MOTHER! THOU ART THE SACRED VESSEL! - Vincent Sekhar (Journal of Dharma, 2012)
It is more than evident that our environment is in crisis. The Hindu Survey of the Environment 2008 states that despite several Governmental and non-Governmental organizations’ efforts, waste management and pollution control remain a big challenge and their solutions are met with little success in India:Electronic trash and biomedical refuse are ever increasing, resulting in infections and other hazards. The climatic change and the growing earth warming is a researched fact due to higher carbon emissions from human activity. Harnessing the power of the sun like in Solar Energy is becoming revolutionary in lighting the billions of life. Wetlands and water banks, which provide many services to local communities, are under threat and evidences indicate that solutions to protect coastal ecosystems are far from satisfactory. Needless to say that sustainable transport future may land us in undertaking fewer, shorter trips, greater use of public transport, number of walking and cycle trips. Problems abound on the issue of Genetically Modified crops, its health and other risk factors, conservation of forest and wild life, extinction of rare species, etc.